Corpus callosotomy outcomes in pediatric patients: A systematic review. (29th May 2016) - Graham, David; Tisdall, Martin M.; Gill, Deepak
Summary: Objective: Corpus callosotomy is a palliative neurosurgical treatment for patients with either generalized or multifocal refractory epilepsy and injurious drop attacks. This report aims to systematically review the pediatric literature. Methods: Medline, Embase, Web of Knowledge, and Scopus were searched systematically for published articles on treatment outcomes of corpus callosotomy for refractory epilepsy. Studies were included if the patient population was younger than 18 at the time of surgery and median follow‐up was >1 year. Studies were excluded if resective surgery was also performed. Results: A total of 12 articles met inclusion criteria. All articles were retrospective case series, with the exception of one being a prospectively designed retrospective case series. There was very little agreement among authors on the definition of a good seizure outcome. Articles that used the Engel classification found that 88.2% of total corpus callosotomy patients had a worthwhile reduction in seizures compared with 58.6% of patients who underwent anterior corpus callosotomy (p < 0.05). Drop attacks improved from corpus callosotomy more than other generalized seizure types. Reported complications were minor in all but one patient, and one death was reported. Transient disconnection syndrome was significantly more likely in total corpus callosotomy than in anterior corpus callosotomy (12.5% vs. 0%; p < 0.05). Improvements in quality of life, behavior, and intelligence/development quotient, as well as parental satisfaction, were generally correlated with seizure outcome. There was no postcallosotomy change in the number of antiepileptic drugs. Significance: Total corpus callosotomy was significantly more likely to result in a reduction in seizures. Anterior corpus callosotomy was unlikely to result in disconnection syndrome. Although all of the papers drew a similar conclusion, the quality of evidence was low. At best, the evidence raises the hypothesis that corpus callosotomy is a safe and effective treatment for refractory generalized epilepsy. It is clear that a case–control or randomized trial is warranted.